2023
DOI: 10.1039/d2gc04414e
|View full text |Cite
|
Sign up to set email alerts
|

High performance, recyclable and sustainable by design natural polyphenol-based epoxy polyester thermosets

Abstract: Renewable flavonoids and phlorotannins extracts were used as building blocks to synthesize biobased tris-epoxy monomers and further to design and develop sustainable thermosetting resins. The triglycidyl ethers of phloroglucinol and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…In their place, two new peaks emerge: one at 1732 cm −1 , indicative of ester carbonyl groups, and another at 3436 cm −1 , corresponding to hydroxyl groups. 33,34 This observation confirms that succinic anhydride effectively reacts with the epoxy groups in ENR, resulting in the formation of ester and hydroxyl groups.…”
Section: ■ Results and Discussionsupporting
confidence: 62%
“…In their place, two new peaks emerge: one at 1732 cm −1 , indicative of ester carbonyl groups, and another at 3436 cm −1 , corresponding to hydroxyl groups. 33,34 This observation confirms that succinic anhydride effectively reacts with the epoxy groups in ENR, resulting in the formation of ester and hydroxyl groups.…”
Section: ■ Results and Discussionsupporting
confidence: 62%
“…High‐performance resins play a critical role in a wide range of technology applications due to their exceptional properties. These advanced resins offer high strength, stiffness, and dimensional stability across a broad temperature range, making them suitable for use in high‐performance components within industries such as aerospace, defense, and electronics 1–3 . The superior thermal and chemical resistance of these resins make them ideal for use in high‐temperature environments and harsh chemical environments, where weight reduction, thermal protection, and durability are required 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…These advanced resins offer high strength, stiffness, and dimensional stability across a broad temperature range, making them suitable for use in high-performance components within industries such as aerospace, defense, and electronics. [1][2][3] The superior thermal and chemical resistance of these resins make them ideal for use in high-temperature environments and harsh chemical environments, where weight reduction, thermal protection, and durability are required. 4,5 They can be used as matrices in fiber-reinforced composite materials, which are rapidly replacing metals in many applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Alice Mija, [28][29][30] Jomin Thomas 31,32 et al reported the application of bio-based or vegetable oil epoxide, which could potentially compete with waterborne systems.…”
Section: Introductionmentioning
confidence: 99%